Wilkie’s syndrome: Laparoscopic management – A case report with review of the literature - Shetty, Shreya; Joshi, Abhijit (Indian Journal of Case Reports, 2022)
Superior mesenteric artery (SMA) syndrome also known as Wilkie’s Syndrome is a rare condition characterized by symptoms of small bowel obstruction. It is caused when the angle between the SMA and aorta, also known as the aorto-mesenteric angle, reduces to